Recent developments in capillary and microchip electroseparations of peptides (2015-mid 2017) - Kašička, Václav (Electrophoresis, 2018)
The review brings a comprehensive overview of recent developments and applications of high performance capillary and microchip electroseparation methods (zone electrophoresis, isotachophoresis, isoelectric focusing, affinity electrophoresis, electrokinetic chromatography, and electrochromatography) to analysis, microscale isolation, purification, and physicochemical and biochemical characterization of peptides in the years 2015, 2016, and ca. up to the middle of 2017. Advances in the investigation of electromigration properties of peptides and in the methodology of their analysis (sample preseparation, preconcentration and derivatization, adsorption suppression and EOF control, and detection) are described. New developments in particular CE and CEC methods are presented and several types of their applications to peptide analysis are reported: qualitative and quantitative analysis, determination in complex (bio)matrices, monitoring of chemical and enzymatical reactions and physical changes, amino acid, sequence and chiral analysis, and peptide mapping of proteins. Some micropreparative peptide separations are shown and capabilities of CE and CEC methods to provide important physicochemical characteristics of peptides are demonstrated.
Keywords: Capillary electrochromatography; Stereoisomerism; Microarray Analysis; chemická frakcionace; Chemical Fractionation; Capillary electrophoresis; peptidové mapování; elektroforéza kapilární; Review; Peptide Mapping; Peptides; stereoizomerie; mikročipová analýza; zvířata; Humans; peptidy; Electrophoresis, Capillary; aminokyseliny; Proteins; lidé; Amino Acids; Animals